Adventures of an occasional click chemist - Bunz, Uwe H. F. (Synlett, 2013)
In this account, I describe my and my group’s adventures in the field of 1,3-dipolar cycloaddition reactions of alkynes to organic azides. Three different topics are treated: post-functionalization and crosslinking of polymers of the poly(phenylene ethynylene) type, the synthesis of conjugated heterocyclic polymers by clicking aromatic diazides to aromatic diynes, and the synthesis of fluorophore dyes that bind to metal cations. In the last case, as a result of the presence of a binding pocket created by a triazole nitrogen and the nitrogen of a neighboring heterocycle (pyridine, chalcodiazole, or phenazine), the binding event leads to specific changes in the absorption and emission spectra of the complex. This account is limited exclusively to experiments performed by our group, as the topic of 1,3-dipolar cycloadditions of azides to alkynes has already been the subject of many comprehensive reviews and accounts. - - 1 Introduction - - 2 Polymeric Clicks - - 3 Metallosensors by Click Chemistry - - 4 Outlook and Conclusion